2021
DOI: 10.37201/req/050.2021
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and outcomes of 1,331 patients with COVID-19: HM Spanish Cohort

Abstract: Background. Spain is one of the European countries most affected by the COVID-19 pandemic. Epidemiologic studies are warranted to improve the disease understanding, evaluate the care procedure and prepare for futures waves. The aim of the study was to describe epidemiologic characteristics associated with hospitalized patients with COVID-19. Methods. This real-world, observational, multicenter and retrospective study screened all consecutive patients admitted to 8 Spanish private hospitals. Inclusion criteria:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Activated monocytes produce inflammatory cytokines and chemokines, which stimulate neutrophils, lymphocytes, platelets, vascular endothelial cells, and monocytes to express tissue factors and phosphatidylserine and trigger coagulation [37,47]. Moreover, abnormal platelet count has previously been related to IMV requirement and different complications in patients with community-acquired pneumonia admitted to intensive care units [48,49] and COVID-19, in which increased platelet consumption has been suggested [48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activated monocytes produce inflammatory cytokines and chemokines, which stimulate neutrophils, lymphocytes, platelets, vascular endothelial cells, and monocytes to express tissue factors and phosphatidylserine and trigger coagulation [37,47]. Moreover, abnormal platelet count has previously been related to IMV requirement and different complications in patients with community-acquired pneumonia admitted to intensive care units [48,49] and COVID-19, in which increased platelet consumption has been suggested [48].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding blood cells, we found significant differences in leukocytes and platelets counts among IMV and non-IMV groups, but not for lymphocytes. Higher leukocytes levels can be due to a coinfection, as observed in patients with COVID-19 and a positive culture for bacteria and fungus, associated with high mortality risk in COVID-19 patients [49,50]. It has been reported that the enhanced inflammatory state, thrombi formation, and platelet consumption can lead to thrombocytopenia, while the cytokine storm causes thrombocytosis [37].…”
Section: Discussionmentioning
confidence: 99%
“…It has also generated critical social problems throughout the world. This infection continues to spread, with more than 200 million confirmed cases and 223 countries, areas, or territories [2].Spain has been one of the European countries most affected by the COVID-19 pandemic as of Mach 17th, with more than 11 000 cases and 491 deaths [3]. Spain had one of the highest…”
mentioning
confidence: 99%
“…Spain has been one of the European countries most affected by the COVID-19 pandemic as of Mach 17th, with more than 11 000 cases and 491 deaths [3]. Spain had one of the highest…”
mentioning
confidence: 99%